Public policy responses to the COVID-19 epidemic: The case of family policy in the Czech Republic - Robert Jahoda; Ivan Malý; David Špaček (Scientific Papers of the University of Pardubice, Series D: Faculty of Economics and Administration, 2021)
Families with dependent children are among the social groups most affected by the COVID-19 pandemic. This paper examines the development of measures applied by the Czech national government for compensating families with children during the COVID-19 crisis. It summarizes the aims of the measures as announced by the government or its ministries. This is supplemented by a summary of the available opinions of experts and other policy stakeholders. Based on this, the paper discusses the adequacy of the adopted measures and points out lessons for the future policymaking in the given area. A relatively high number of measures were identified. This suggests that the government strived for proactive policy to address families as a vulnerable social group. However, a rapid and sometimes unrestrained legislative process seems to have come at the expense of a proper public debate on the need for and impact of the new measures. Given the uncertain time horizon of the epidemic, the apparent lack of consideration regarding the budgetary implications of the measures seems worrying.
Keywords: H2; H3; H5; 330; Czech Republic; Public Policy; Covid-19; Policy-Making; Policy Learning; Family Policy